Relationship between metal inhibition and microbial products in biological systems - Geyik, Ayşe Gül. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2015., 2015)
One of the main topics in biological treatment systems is the production of extracellular polymeric substances (EPS) on surface of cells. These substances consisting mainly of proteins and carbohydrates have the ability to bind metals. In this dissertation, first activated sludge reactors were operated in long term at different COD/TKN ratios and with different organic substrates. In each sludge EPS production as well as the changes taking place in EPS were examined. The study pointed to the existence of a very loosely bound EPS fraction in sludge of which there was no mention in literature before. In addition, the study examined the relationship between EPS and surface charge and hydrophobicity of sludges. The results indicated that in an activated sludge system wastewater composition was of crucial importance and the composition of EPS varied with the feed supplied to an activated sludge system. The inhibitory effect and binding of silver and nanosilver (AgNP) was studied. AgNP was synthesized in laboratory. Although the concentration of nanosilver was raised to levels above the normal concentrations found in sewage, nanosilver had no effect on substrate removal since it lost its stability. However, the presence of nanosilver clearly affected the structure of EPS. The binding of nanosilver to the various fractions in EPS is of importance since this determines the transfer of nanosilver to the receiving water or accumulation in sludge phase. Overall, the study revealed that “heavy metal inhibition” depended on many factors.
Keywords: Biological systems.